<The> File Office Programs Microsoft Office - Place in Pc Software, Development, Structure, Focus of Individual Programs - Dugas, Jaroslav, 1967-
Office 2019 pre študentov a domácnosti – Office Home and Student 2019. Office 2019 pre podnikateľov. Office 2019 Professional. Word – Microsoft Word. Word pre študentov a domácnosti. Excel – Microsoft Excel. Excel pre študentov a domácnosti. Outlook – Microsoft Outlook. PowerPoint – Microsoft PowerPoint. PowerPoint pre študentov a domácnosti. Access. Project Standard 2019. Project Professional 2019. Visio Standard 2019. Visio Professional 2019. Office 365 Home. Office 365 Personal. Office 365 Business. Office 365 Business Premium. Office 365 Business Essentials. Yammer.